2017
DOI: 10.3390/w9120979
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Performance for Treatment of Cr (VI)-Containing Wastewater by Microbial Fuel Cells with Natural Pyrrhotite-Coated Cathode

Abstract: Abstract:Here we reported the investigation of enhanced performance for the removal of hexavalent chromium (Cr (VI)) by a new microbial fuel cell (MFC) with natural pyrrhotite-coated cathode. By comparisons of the graphite-cathode, the MFCs equipped with a pyrrhotite-coated cathode generated the maximum power density of 45.4 mW·m −2 that was 1.3 times higher than that of with bare graphite cathode (35.5 mW·m −2 ). Moreover, the Cr (VI) removal efficiency of 97.5% achieved after 4.5 h compared with only 46.1% b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…To gain a better understanding of the performance of wolframite photocathodes MFC, their power density was compared with MFCs in recent studies with different types of catalysts. For example, the maximum power density of a natural hematite-coated cathode MFC was 144.4 ± 7.5 mW m −2 [19], which was 45.4 mW•m −2 in a natural pyrrhotite-coated cathode MFC [20]. Moreover, manganese oxides nanoparticles and lead oxides were characterized as the cathode materials for MFCs, and the maximum power density of MnOx/C-MFC was 161 mW•m −2 [16], and 22.1, 97.8, 82.6, and 78 mW•m −2 for α-MnO2, β-MnO2, γ-MnO2, and PbO2-coated air cathode microbial fuel cells, respectively [15,18].…”
Section: Mfc Performance Analysismentioning
confidence: 97%
See 1 more Smart Citation
“…To gain a better understanding of the performance of wolframite photocathodes MFC, their power density was compared with MFCs in recent studies with different types of catalysts. For example, the maximum power density of a natural hematite-coated cathode MFC was 144.4 ± 7.5 mW m −2 [19], which was 45.4 mW•m −2 in a natural pyrrhotite-coated cathode MFC [20]. Moreover, manganese oxides nanoparticles and lead oxides were characterized as the cathode materials for MFCs, and the maximum power density of MnOx/C-MFC was 161 mW•m −2 [16], and 22.1, 97.8, 82.6, and 78 mW•m −2 for α-MnO2, β-MnO2, γ-MnO2, and PbO2-coated air cathode microbial fuel cells, respectively [15,18].…”
Section: Mfc Performance Analysismentioning
confidence: 97%
“…It is worthwhile mentioning that Ren et al first investigated the utilization of natural hematite as a cathode catalyst in a traditional MFC, which indicated that the maximum power density in a hematite-coated cathode MFC was 2.2 times higher than that in a graphite cathode MFC, and a current density of 330.66 mA•m −2 was stabilized over 10 days [19]. Shi et al studied the performance and Cr(VI) removal efficiencies by natural pyrrhotite-coated cathode MFCs and demonstrated that the natural pyrrhotite not only played the role of catalyst, but also acted as a reactive site for Cr(VI) reduction [20]. It must also be mentioned that Lu et al used the semiconducting mineral natural rutile as a novel photocathode catalyst for MFCs, which produced a maximal power density of 7.64 and 12.03 W•m −3 under dark and light irradiation, and provided a cost-effective alternative photocatalyst from nature [21].…”
Section: Introductionmentioning
confidence: 99%
“…The experimental results showed a high reduction rate of 2.13 g/m 3 -h with achievable maximum power density and current density of 1540 mW/m 2 and 4560 mA/m 2 (see Figure 11) [165]. Shi et al investigated graphite electrode modified with natural pyrrhotite for the reduction of Cr 6+ in the MFC [166]. A removal of 99.59% was achieved within 10.5 h of operation with a maximum power density of 45.4 mW/m 2 .…”
Section: Nanomaterials Modified Cathode Materialsmentioning
confidence: 99%
“…Since the determination of Pseudomonas dechromaticans as the first described Cr(VI) reduction microbe [38], research regarding Cr(VI) reducing bacteria has continued and a lot of information has been col-lected about Cr(VI) reduction in laboratory and field conditions [39]. Thus, there is various evidence showing the efficiency of numerous bacteria in Cr(VI) reduction [40].…”
Section: Bacterial Isolates and Their Growth Kinetics And Cr(vi) Reduction Potentialmentioning
confidence: 99%